Um percurso artístico: do Zanni ao sujeito performático - Bortoluzzi, Gilvani José (2018)
The contemporary art is built on a path that proclaims, among other things, the plurality of artistic manifestations. Transdisciplinary pathways are quite recurrent in this context. So, the present dissertation text discusses an investigation developed in the PPGART / CAL of the Federal University of Santa Maria (UFSM) in Visual Poetics in contemporary art, inserted in the research line Art and Culture. The objective of the study consisted, initially, in the elaboration of a poetic, based on the crisscrossing between the Theater and an Art Performance in its approaches in the contemporary art. His poetic journey was made by the displacement of a theatrical personage originating from Commédia Dell’arte, constructed from an autobiographical text for a subject of performance actions. To support this course, he relied on theorists Cohen, Glusberg, Goldberg, Phelan and Taylor. Dario Fo also based his methodological creation procedures on Commédia Dell’arte. The creation was done from theoretical research, field research and in laboratories through improvisations. This research was based on the characteristics of Zanni, a typical character, from the Commédia Dell’arte, popular Italian culture of the XVI century. The intention was to potentiate the Zanni as an instituting figure of the performative work. This manifestation happened between the popular layers like form of expression, denouncing the terrible conditions to which they were submitted. It was glimpsed that his detonating posture of social issues of the time was approaching Performance Art as a transgressive language. Thereafter, two series of Performances were performed. In the first series I developed a work titled afterwards of Pre-Performance. In this first series were realized three versions of Performances, O Zanni Performer vendendo ilusões I, II and III. The second series focuses on environmental issues and has three Performances. The first was the name of the series, O Zanni Performer no Lixão, the second Aqui ou Alixo and the third was Reciclando (Des) Ilusões. Thus, the research entitled An Artistic Path: from the Zanni to the Performing Subject, came to meet both the presuppositions of contemporary performative art and political-social issues, being shaken by the outbursts of the political class. Therefore, the realization of these Performances was a social critic at the same time that it opportunized a way of the artist to update the Zanni and to construct a reflection on the contemporary art.